Improvement in the ideal range of vault after implantable collamer lens implantation: a new vault prediction formula - Wu, Hao; Zhong, Ding-juan; Luo, Dong-qiang; Zhang, Li-yuan; Liu, Jia; Wang, Hua (Frontiers in Medicine, 2023)
Background To derive and validate a novel vault prediction formula to improve the predictability and safety of implantable collamer lens (ICL) implantation. Methods Thirty-five patients (61 eyes) with previous posterior chamber intraocular lens implantation were included. Various parameters, such as horizontal-visible iris diameter (HVID), photopic pupil diameter (PPD), axial length (AL), white-to-white (WTW), anterior chamber width (ACW), angle-to-angle (ATA), crystalline lens rise (CLR), anterior chamber depth (ACD), horizontal sulcus-to-sulcus (HSTS), and ciliary sulcus angle (CSA) were measured. Vault was measured at 3 months after surgery using CASIA2 anterior segment optical coherence tomography. The formula was derived using multiple linear regression analysis and named as WH formula. It was validated in 65 patients (118 eyes) to determine the percentage of the ideal postoperative vault range and to compare the differences between the WH formula and the NK, KS, and STAAR formulas. Results Final ICL size, ATA, CSA, and CLR were included in the prediction formula model (adjusted R2 = 0.67, p < 0.001). The achieved vault 1 month after the surgery was 556.19 μm ± 166.98 μm in the validation group, and the ideal vault range was 200–800 μm (92%). The difference between the achieved vault and that predicted using the WH formula was not statistically significant (p = 0.165), whereas the difference between the achieved vault and that predicted using the NK and KS formulas was statistically significant (p < 0.001 and p < 0.001, respectively). The 95% agreement limit range of the achieved vault and the vault predicted using the WH formula was narrower than those predicted using the NK and KS formulas (−295.20–258.82 μm). Conclusion This study combined the results of optical coherence tomography and ultrasound biomicroscopy measurements of the anterior segment of the eye and incorporated ciliary sulcus morphology quantification into the prediction formula. The study derived a prediction formula for vault by combining ICL size, ATA, and CLR. The derived formula was found to be superior to the currently available formulas.